Nanomechanics serving polymer-based composite research - Pardoen, Thomas; Klavzer, Nathan; Gayot, Sarah; van Loock, Frederik; Chevalier, Jérémy; Morelle, Xavier; Destoop, Vincent; Lani, Frédéric; Camanho, Pedro; Brassart, Laurence; Nysten, Bernard; Bailly, Christian (Comptes rendus. Physique, 2021)
Tremendous progress in nanomechanical testing and modelling has been made during the last two decades. This progress emerged from different areas of materials science dealing with the mechanical behaviour of thin films and coatings, polymer blends, nanomaterials or microstructure constituents as well as from the rapidly growing field of MEMS. Nanomechanical test methods include, among others, nanoindentation, in-situ testing in a scanning or transmission electron microscope coupled with digital image correlation, atomic force microscopy with new advanced dynamic modes, micropillar compression or splitting, on-chip testing, or notched microbeam bending. These methods, when combined, reveal the elastic, plastic, creep, and fracture properties at the micro-and even the nanoscale. Modelling techniques including atomistic simulations and several coarse graining methods have been enriched to a level that allows treating complex size, interface or surface effects in a realistic way. Interestingly, the transfer of this paradigm to advanced long fibre-reinforced polymer composites has not been as intense compared to other fields. Here, we show that these methods put together can offer new perspectives for an improved characterisation of the response at the elementary fibre-matrix level, involving the interfaces and interphases. Yet, there are still many open issues left to resolve. In addition, this is the length scale, typically below 10 micrometres, at which the current multiscale modelling paradigm still requires enhancements to increase its predictive potential, in particular with respect to non-linear plasticity and fracture phenomena.